The Effect Of Competence, Motivation, And Family Environment On The Work Readiness Of 12th Grade Students At Smk N 2 Rembang Before Entering The Workplace - Fadlila Romadhani Erlini H; Ming Ming Lukiarti (Jurnal Economic Resource, 2026)
The purpose of this study was to demonstrate the influence of competence, motivation, and family environment on the work readiness of 12th-grade students at SMK N 2 Rembang before entering the workforce. This study used independent variables: competence, motivation, and family environment, with work readiness as the dependent variable. Data collection was conducted through a questionnaire. The data source used in this study was primary data obtained from a questionnaire completed by respondents. The study population consisted of all 12th-grade students at SMK N 2 Rembang, graduating class of 2025, with a sample size of 90. Data analysis used multiple linear regression. The results showed that competence had a significant positive effect on the work readiness of 12th-grade students at SMK N 2 Rembang before entering the workforce. Motivation had a positive but insignificant effect on the work readiness of 12th-grade students at SMK N 2 Rembang before entering the workforce. The family environment had a significant positive effect on the work readiness of 12th-grade students at SMK N 2 Rembang before entering the workforce.